Knowledge management and its impact on organizational performance: Evidence from Pakistan - Mohd Sadad, Mahmud; Muhammad Bilal, Majid (2019)
The aim of this research is to investigate the impact of knowledge management on organizational performance with the moderating role of transformational and Participative leadership behavior in telecom sector of Punjab, Pakistan. How leaders motivate to their employees and how they enhance the performance of organizations by using their knowledge. Research approach was deductive. Postivism research paradiagm was used to measure the study. Simple random sampling technique was used to collect data from employees as well as managers of telecom sector. Sample size was 280 employees of telecome sector. This research is significant for academically and practically in public and policy making. How an organization can enhance to their performance, effectively when long-term commitment, trust, successful socialization of employees and organizational citizenship behavior take place in the organization.